1995
DOI: 10.1007/bf02736757
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, pharmacological characterization, and anatomical distribution of a rat cDNA encoding for a galanin receptor

Abstract: We have cloned and expressed a rat cDNA, designated GALR1-rat, that encodes a galanin receptor based on homology, pharmacology, and anatomical criteria. This cDNA was isolated from a rat brain cDNA library. The nucleotide sequence of the cloned receptor revealed an open reading frame encoding a 346-amino-acid protein, showing 90.8% identity with the previously cloned human galanin receptor. Membranes prepared from COS cells transiently expressing GALR1-rat specifically bind 125I-galanin with high affinity (Kd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 24 publications
12
133
1
Order By: Relevance
“…Several differences were evident in the distribution pattern of GALR1 mRNA between the mouse and that previously reported in the rat (Burgevin et al, 1995;Gustafson et al, 1996;Mitchell et al, 1997;O'Donnell et al, 1999;Parker et al, 1995;Waters and Krause, 2000). In the telencephalon, we found many GALR1 mRNA-positive cells throughout the rostral to caudal extent of the caudate putamen.…”
Section: Distribution Of Galr1 In the Forebrain Of The Mousecontrasting
confidence: 55%
See 1 more Smart Citation
“…Several differences were evident in the distribution pattern of GALR1 mRNA between the mouse and that previously reported in the rat (Burgevin et al, 1995;Gustafson et al, 1996;Mitchell et al, 1997;O'Donnell et al, 1999;Parker et al, 1995;Waters and Krause, 2000). In the telencephalon, we found many GALR1 mRNA-positive cells throughout the rostral to caudal extent of the caudate putamen.…”
Section: Distribution Of Galr1 In the Forebrain Of The Mousecontrasting
confidence: 55%
“…Two of these, galanin receptor 1 (GALR1) and galanin receptor 2 (GALR2), are highly expressed in the rat brain (Burgevin et al, 1995;Gustafson et al, 1996;Mitchell et al, 1997;O'Donnell et al, 1999;Parker et al, 1995;Waters and Krause, 2000). While a preliminary report of the distribution of GALR2 in the mouse has been published , no anatomical studies in the brain exist for GALR1 in this species.…”
mentioning
confidence: 99%
“…Moreover, in vivo galanin can modulate 5-HT 1A preand postsynaptic receptor functions in an antagonistic manner (see Fuxe et al, 1998;Misane et al, 1998; The action of galanin is mediated via three G proteincoupled receptors, GalR1-GalR3 (see Branchek et al, 2000), which are expressed in the LC, DR, and their projection areas (Xu et al, 1998b, c;O'Donnell et al, 1999;Burazin et al, 2000;Larm et al, 2003;Hawes and Picciotto, 2004;Hawes et al, 2005;Swanson et al, 2005). Among these receptors, GalR1 and GalR3 mainly activate G i/o types of G proteins mediating inhibitory actions of galanin (Habert-Ortoli et al, 1994;Burgevin et al, 1995;Parker et al, 1995;see Branchek et al, 2000). In contrast, the GalR2 subtype can transmit either stimulatory effects of galanin, for example, on neurotransmitter release, acting via G q/11 types of G proteins (Smith et al, 1997;Wang et al, 1997;Fathi et al, 1998), or it can inhibit neurotransmission via G i/o types (Fathi et al, 1998;Wang et al, 1998;see Branchek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Galanin decreases presynaptic DA release in striatal slices (Tsuda et al, 1998) and one possible explanation for the heightened sensitivity of GKO mice to morphine-induced locomotion and CPP is that knockout of the peptide may result in hyperactivation of DA signaling following opiate administration. Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All three galanin receptor subtypes, as well as significant galanin binding, are found in the ventral tegmental area (VTA), amygdala, nucleus accumbens (NAc), cingulate cortex, and locus coeruleus (LC) (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), areas of the brain known to contribute to drug addiction and reward. Galanin also regulates the levels and release of a number of neurotransmitters, including dopamine, acetylcholine, and norepinephrine (Pieribone et al, 1995;Tsuda et al, 1998;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%